Convenient Election Conflict Management (Case Study of the 2018 South Central Elections) - Oktavianus Anggriawan Kedabu (International Journal Labs, 2022)
Background: The 2018 TTS Pilkada conflict was caused by incomplete and inauthentic documents to conduct the election, namely the original hologram C1-KWK model form and the original hologram C1 Plano-KWK model form at 30 polling stations. Objective: Describe and analyze the Conflict Management of the South Central Timor Regency Pilkada in the 2018 Simultaneous Regional Head Elections. Methods: qualitative. Research Location : South Central Timor Regency. Research focus: Third Party Intervention Model Conflict Management which consists of conciliation, negotiation, mediation and arbitration. Informant determination technique: purposive sampling. Data collection techniques: interviews and documentation. Results: Negotiation: The TTS KPU meeting with Paslon No.2 occurred at the stage of the dispute over the election results aimed at discussing the findings that became objections to Paslon No.2 in the 2018 TTS Pilkada. The meeting was attended by Paslon No.2 along with several TPS witnesses and the success team and from security.